Psychosocial stress in pregnancy and its relation to the onset of premature labour. Issue 6187 (18th August 1979) - Newton, R W; Webster, P A; Binu, P S; Maskrey, N; Phillips, A B
Abstract : A modified life events inventory was presented over a four-month period to 132 consecutive women going into spontaneous labour in Hull and Manchester. Three study groups were identified according to the duration of pregnancy. The levels of psychosocial stress in pregnancy were found to be particularly high in the mothers whose babies were born preterm. Stressful events may precipitate preterm labour in some women. The concept of antenatal care may have to be broadened if the incidence of premature labour and resulting perinatal mortality are to be reduced.